Security of European critical infrastructures outside the European Union: a review of the Western Balkans national laws - Milica Sikimić (Insights into Regional Development)
From the very beginning of the 21st century, the European Union took measures to develop a common security framework for critical infrastructure protection and to harmonize measures and standards between states. European critical infrastructures should be determined from the national critical infrastructure, which implies the regulations / rules for critical infrastructure protection are an important factor in European security and national laws. The paper examines the representation and impact of the provisions of DIRECTIVE 2008/114 / EC in the specific laws for security and protection of European critical infrastructures outside the European Union. In the Western Balkans, four specific laws were adopted setting out national frameworks for the establishment of critical infrastructure protection frameworks. The results of the analysis are based on the incorporation and implementation of the suggested common European Union approach for critical infrastructure protection in the national legislations of Western Balkan countries. Keywords: European critical infrastructures, security, national laws, Western Balkans.